Classificatory disputes and scientific controversies: society, nature, and culture in the Anthropocene (Sustainability in Debate, 2021)
In general, the idea of Anthropocene refers to the set of socio-historical, ecological, economic, and technological transformations responsible for configuring a new stage of regulation and evolution of the planetary geological system. From its original proposition in the 2000s, this notion gained increasing repercussion, mobilizing different positions in multiple fields of scientific knowledge. This article aims to develop a critical analysis of some of the main concepts found in such debates, from the mobilization of three fundamental analytical categories: the concepts of Society, Nature, and Culture. In methodological terms, this is a literature review article based on qualitative and non-systematic bibliographic research. The analysis undertaken here indicates how the different approaches mobilized by the driving idea of Anthropocene result in theoretical movements that redefine the relationships between agency, structure, and social change in the historical context of modern industrial societies.